2017
DOI: 10.1007/s00198-017-4307-6
|View full text |Cite
|
Sign up to set email alerts
|

CT-based evaluation of volumetric bone density in fragility fractures of the pelvis—a matched case-control analysis

Abstract: level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 29 publications
0
17
0
1
Order By: Relevance
“…The present study used DEXA to evaluate the TBMD as a primary endpoint in rats fed with the KD. DEXA is the gold standard for the diagnosis of osteoporosis, and the T-score is highly correlated with the fracture risk (32). While the present results indicated an obvious decrease in the TBMD in the KD group, the bone loss within certain specific bones required further evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…The present study used DEXA to evaluate the TBMD as a primary endpoint in rats fed with the KD. DEXA is the gold standard for the diagnosis of osteoporosis, and the T-score is highly correlated with the fracture risk (32). While the present results indicated an obvious decrease in the TBMD in the KD group, the bone loss within certain specific bones required further evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the methods used in previous studies, 5,6,16 the ROIs in our study were manually placed in the center of midaxial and midsagittal images of the S1 bodies. The reliability of our measurements was excellent with ICCs comparable to those in the study by Katsuura et al 6 To our knowledge, this is the first study to show the significant correlation between HUs of the S1 body and DXA T-scores, and we found that their Pearson correlation coefficients were comparable to those between HUs of L1-5 and DXA T-scores in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Since lumbar CT is a common examination performed for patients requiring surgery for lumbar degenerative diseases, HUs can be used to evaluate BMD at no extra cost and radiation. There have been a few studies involving the manual measurement of HUs of the S1 body from clinical CT scans, 5,6,16 which support the use of HUs to determine sacral BMD. However, the correlation of HUs of the S1 body with DXA T-scores and the diagnosis of osteoporosis has not been explored.…”
mentioning
confidence: 99%
“…Thus, the region of interest in S1 must be carefully selected, in order to avoid areas with extreme high or low density. This could be a reason that the values for S1 are less accurate than published values for L1-L2 [17][18][19]. However, the results for S1 comfortably reached significance, too, allowing us to assume that the methodology presented is suitable for both the lumbar and the sacral spine.…”
Section: Discussionmentioning
confidence: 76%